Peningkatan Kesadaran Pengelolaan Sampah dan Optimalisasi Digital untuk UMKM di Kelurahan Tonja, Kecamatan Denpasar Utara, Kota Denpasar - Cokorda Krisna Yudha; Ni Luh Putu Indiani (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2024)
Tonja Village is one of the sub-districts located in North Denpasar District, Denpasar City, Bali. Tonja Village has strong economic potential, especially through the trade sector. The large number of residents involved in trade creates opportunities for the development of small and medium enterprises (SMEs) as well as improving the local economy. Of the various challenges identified, the two main problems that were the focus of the intervention were the lack of public awareness about good waste management and the difficulties experienced by Micro, Small and Medium Enterprises (MSMEs) in understanding and optimizing the use of digital platforms. The